2019
DOI: 10.1126/sciadv.aav4324
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-Cas9 corrects Duchenne muscular dystrophy exon 44 deletion mutations in mice and human cells

Abstract: Mutations in the dystrophin gene cause Duchenne muscular dystrophy (DMD), which is characterized by lethal degeneration of cardiac and skeletal muscles. Mutations that delete exon 44 of the dystrophin gene represent one of the most common causes of DMD and can be corrected in ~12% of patients by editing surrounding exons, which restores the dystrophin open reading frame. Here, we present a simple and efficient strategy for correction of exon 44 deletion mutations by CRISPR-Cas9 gene editing in cardiomyocytes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
263
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 211 publications
(272 citation statements)
references
References 40 publications
8
263
0
1
Order By: Relevance
“…Studies on delivery have been limited, however, owing to the more prevalent use of in vitro hiPSC systems for research. Interestingly, studies from DMD models suggest that the heart is surprisingly well-favored for viral vector-based delivery of genome editing agents [106][107][108][109][110][111]113,163]. It would be interesting to see if this is the case for other in vivo cardiomyopathy models or how non-viral means of delivery may compare.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on delivery have been limited, however, owing to the more prevalent use of in vitro hiPSC systems for research. Interestingly, studies from DMD models suggest that the heart is surprisingly well-favored for viral vector-based delivery of genome editing agents [106][107][108][109][110][111]113,163]. It would be interesting to see if this is the case for other in vivo cardiomyopathy models or how non-viral means of delivery may compare.…”
Section: Resultsmentioning
confidence: 99%
“…In one study, tripling the dose of a single Cas9-gRNA vector increased the number of dystrophin-positive fibers to about 40%, when initially there were only a few, scattered dystrophin-positive fibers present in the heart [112]. Min et al (2019) published an interesting study on dosing, which showed that the ratio of Cas9 to gRNA vector amounts administered in vivo was a critical determinant of therapeutic efficacy [113]. In the study, they treated mice carrying a deletion in Dmd exon 44 through the CRISPR-mediated skipping or reframing of exon 45.…”
Section: Studies Using Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In their most recent work, the research group have demonstrated the ability of the CRISPR/Cas9 system to correct the deletion mutation of exon 44 of the DMD gene in mice and human iPSC-derived cardiomyocytes [11]. They found that when targeting this section of the gene, a different region to that targeted in their previous studies, the standard 1-to-1 ratio of Cas9 and guide RNA was not as effective.…”
Section: The Power Of Strengthmentioning
confidence: 99%
“…Dystrophin (red) restoration shown in a CRISPR edited DMD-affected heart muscle cell (right) relative to unedited cell (left) [11]. …”
Section: The Power Of Strengthmentioning
confidence: 99%